PENDIDIKAN KARAKTER PEDULI LINGKUNGAN MELALUI PROGRAM ADIWIYATA BERBASIS EKOPEDAGOGIK - Trisni Handayani; Zulela MS; Chrisnaji Banindra Yudha (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2021)
The moral degradation and character of the nation's children is increasingly worrying. This phenomenon can damage the realization of the superior generation of the nation's generation. So it takes a touch in basic education that can provide reinforcement and the formation of student character in loving the environment in a sustainable manner. This study aims to determine the effect of the Adiwiyata program on environmental education based on ecopedagogic-based care for high-class students at Cijantung 03 Jakarta Primary School The research method used is a descriptive associative quantitative approach, a simple paradigm research design. The sample used was stratified random sampling with validity testing using Pearson product-moment correlation. While the reliability test uses Alfa Cronbach. Based on the analysis of the data it can be concluded that the results of this study indicate that there is a significant influence in fostering environmental care character for schools that receive the Adiwiyata-based Ecopedagogic program including habits in maintaining the cleanliness and beauty of the school environment that has an impact on students' habits of maintaining, preserving, and discarding orderliness. rubbish and recycle the garbage in the environment